Understanding the Value of Religious Tolerance Among Adolescents Through the Lens of Lawrence Kohlberg's Moral Development Theory: A Literature Review - Yoga Firmansyah; Nyac Nauva Hasan; Nayla Tsuroya; Imelda Fitriyanda; Aulia Az-Zahra; Ratna Fitria (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze adolescents’ understanding of religious tolerance values through the perspective of Lawrence Kohlberg’s theory of moral development. The research employed a literature review method with a descriptive qualitative approach, supported by field data collected through questionnaires administered to 17 students of MTs At-Taqwa Cihampelas. Data sources were obtained from scholarly journals, books, and previous studies relevant to religious tolerance, adolescent moral development, Pancasila Education, and guidance and counseling services. The findings indicate that the majority of students demonstrated a high level of understanding of tolerance, accounting for 58.82% of respondents, while 41.18% were categorized as having a moderate level of understanding. Analysis based on Kohlberg’s theory revealed a positive trend in moral development, ranging from the pre-conventional stage to the post-conventional stage. The high level of tolerance understanding was reflected in students’ respect for religious differences, tolerant behavior within the school environment, and awareness of the importance of peaceful coexistence. These findings suggest that adolescents’ moral development significantly influences their ability to understand and internalize the values of tolerance. Furthermore, inclusive religious education, Pancasila values, family environment, and social experiences were identified as important factors in shaping tolerant attitudes among adolescents. This study also highlights the crucial role of education and guidance and counseling services in stimulating moral development and strengthening religious tolerance within the school setting.